2020
DOI: 10.18203/2349-2902.isj20201547
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of gallstone disease in an industrial township in India: are the risk factors different?

Abstract: Background: The prevalence of gallstones among different populations is varied, which reflects the role of genetic and environmental factors, besides common factors like age, sex, parity, obesity and diet. Being a commonly treated surgical problem, we attempted to study the epidemiology, risk factors and predisposing factors related to gallbladder disease in our setup- the industrial township of Bharat Heavy Electricals Limited (BHEL), Bhopal, India.Methods: This was an observational study done over a period o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…Fifty-five out of 81 patients (55.56%) had a family history of gallstone disease, similar results were found by others [17,24,33] that confirmed the occurrence of cholelithiasis associated with a family history of gallstone disease. Disagreement with several previous studies reported that biliary stones are associated without a family history of gallstones in various populations [4,34,35] . Some studies suggested that genetics has a significant role in the development of gallstones, where increased frequency of gallstones in the first degree of relatives is a risk factor [25] .…”
Section: Discussioncontrasting
confidence: 79%
“…Fifty-five out of 81 patients (55.56%) had a family history of gallstone disease, similar results were found by others [17,24,33] that confirmed the occurrence of cholelithiasis associated with a family history of gallstone disease. Disagreement with several previous studies reported that biliary stones are associated without a family history of gallstones in various populations [4,34,35] . Some studies suggested that genetics has a significant role in the development of gallstones, where increased frequency of gallstones in the first degree of relatives is a risk factor [25] .…”
Section: Discussioncontrasting
confidence: 79%
“… 4 The prevalence of cholelithiasis differs not p>only between countries but also among different ethnic groups, age groups, and genders, differences in dietary and lifestyle patterns with a preference for junk food and sedentary lifestyles, and the incidence of gallstones is rising globally. 4 , 5 …”
Section: Introductionmentioning
confidence: 99%
“…4 The prevalence of cholelithiasis differs not only between countries but also among different ethnic groups, age groups, and genders, differences in dietary and lifestyle patterns with a preference for junk food and sedentary lifestyles, and the incidence of gallstones is rising globally. 4,5 Since there are very few studies conducted in Nepal regarding the prevalence of cholecystectomy among the patients admitted to the Department of Surgery, this article will be helpful in finding out the data. Hence, the aim of this study was to find out the prevalence of cholecystectomy among patients admitted to the Department of Surgery in a tertiary care centre.…”
Section: Introductionmentioning
confidence: 99%